Determining Standard Levels For Some Complex Offensive Skills In Basketball For Players Of The National Center For Sports Talent Welfare In Diyala (Journal of the College of Basic Education, 2024)
The importance of the research in determining standard levels for the most important offensive skills in basketball came because using a skill test as a criterion may not include all the factors for evaluation despite its importance. The purpose of tests in basketball is to create some standard levels that the coach relies on in determining the players’ physical, skill, and tactical abilities. The study aimed to identify and determine some complex offensive skills in basketball for players of the National Center for Sports Talent Welfare in Diyala, as well as building standard levels for some complex offensive skills in basketball for players of the National Center for Sports Talent Welfare in Diyala. The researcher used the descriptive method using the survey style for its suitability in solving the research problem. The research population was selected from basketball players, The researcher selected the research sample consisting of the players of the National Center for Sports Talent Welfare in Diyala, and their number was (48) players, while the research sample was (36) players, as in Table (1), and the research sample was chosen randomly for one category and age (14-16) year. The research procedures included conducting a test of combined offensive skills using basketball; test (receiving + jumping shot / two points), test (receiving + jumping shot / three points), test (receiving + high plumping + two-handed chest passing). Through analyzing and discussing the research results, the researcher concluded that there are different standard levels and grades for evaluating gifted people at the National Center for Basketball Sports Talent Welfare. The best level of complex offensive skills was distributed at an (B-) level, followed by a (B+) level, and then (C+). The researcher recommends adopting the standard levels and grades that the researcher arrived at in the process of objective evaluation of players in sports talent centers, as well as conducting similar research and studies to determine standard levels for complex defensive skills in basketball.